Effect of moisture and temperature on the extrudate properties of milkfish (Chanoschanos) feed - Raffic Ali, S. Syed; Ambasankar, K.; Balachandran, S.; Ramachandran, K. (Indian Journal of Fisheries, 2019)
The present study evaluated the effect of varying levels of moisture and temperature on the extrudate properties of the milkfish (Chanos chanos) feed containing 31.49% protein and 4.71% lipid. Two trials were conducted in a pilot scale twin screw extruder using 3 mm die. In the first trial, the effect of temperature on extrudate properties was studied at five different temperatures viz., 80-90, 90-100, 100-110, 110-120 and 120-130ÂºC. The results revealed that the temperature levels of 100-110, 110-120 and 120-130ÂºC resulted in significantly (p